Implementasi Kebijakan Transparansi Anggaran Pendapatan dan Belanja Desa (APBDes) : Studi di Desa Doko, Kecamatan Ngasem, Kabupaten Kediri, Jawa Timur - Yorika Wulan Sari (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
This study aims to determine and analyze the implementation of the Village Revenue and Expenditure Budget (APBDes) transparency policy and the obstacles faced in the process in Doko Village, Ngasem District, Kediri Regency. This study uses a qualitative descriptive approach with data collection methods through in-depth interviews, observations, and documentation of various village informants such as village officials, BPD members, and community leaders. The results of the study indicate that the implementation of APBDes transparency in Doko Village has been running quite well, marked by the availability of complete documentation, accessibility of information to the public, openness in every stage of budget management, and the implementation of regulations that support transparency.